Methicillin Resistant Staphylococcus aureus (MRSA) Infection in Canines and its Public Health Importance - Debbarma, Jashima; Rajesh, J. B.; Kar, Payel; Das, Manas; Lucy, Elone; Debnath, Ankita; Debbarma, Binipi; Marwein, S. C.; Rose, K. T.; Christen, C.; et al. (International Journal of Bio-resource and Stress Management, 2025)
This paper reviews about Methicillin-resistant Staphylococcus aureus (MRSA) in canines and its influence in public health. This disease could spread from one species to another, including from people to dogs and vice versa. MRSA in pets was reported in the late 1990s. The clonal types that infect people in the same geographic area connect with those seen in dogs and cats. Globally S. aureus was the main cause of infections linked to health care and the community. MRSA in dog kennels can cause a number of illnesses, such as pyoderma observed that animals have superficial bacterial infections that cause pus-filled skin lesions and signs like pruritus, discomfort, inflammation crusting, pustules, irritation, and even hair loss and deadly pneumonia in pups, and gangrenous mastitis in bitches. Methicillin was one of the antistaphylococcal penicillins to which S. aureus has become resistant. Penicillin binding protein 2a (PBP2a), which had a very low affinity for beta-lactam antibiotics, was encoded by the mecA gene and mediates MRSA resistance. For MRSA infections in animals, conventional antibiotics such as doxycycline, rifampin, clindamycin, trimethoprim-sulfamethoxazole, tetracyclines, and vancomycin could be administered. Improving infection control procedures like hospitals and household was a proven and effective way to reduce the spread of bacteria resistant to antibiotics and other diseases. Biosecurity and disease management programs must be implemented to stop the spread of pathogens to humans. Measures to prevent antibiotic resistance and reduce the spread of disease include vaccination campaigns, animal and handler cleanliness, and sanitation.